Designing Android Based Physical Activities and “Lafit” to Increase Physical Fitness Level of Elderly - Aufan, Rifqi; Handoko, Abdul Harris (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
The elderly so that they can do physical activities anywhere and anytime with the aim of improving their physical fitness so that by increasing their physical fitness then their immune level will also increase so that it can reduce the risk of being exposed to viruses, especially the corona virus. This goal is also to create a special TKJI test application for the elderly so that the elderly can measure their own physical fitness level. The specific target of this research is the people of Laut Dendang Village aged 60 years and over. This application contains learning tutorials to do safe and fun physical activities for the elderly completed with tutorials on how to do physical fitness tests that are packaged in an attractive android application so that they can be accessed by the elderly through their smartphones anytime and anywhere. This research used research and development method by borg and gall through 10 steps from potential and problem until mass production. This research involves FIK Unimed lecturers as models in making videos that contain material for physical activity movements that are safe for the elderly and the videos in this application will be made in a simple and clear way and will go through the editing process using specific software. This research showed that the physical fitness of the elderly people increased considerably.